Development rights and conservation constraints: urban conservation-oriented controls in the City of Cape Town - Townsend, Stephen S (School of Architecture, Planning and Geomatics, 2015)
The primary intention of this study is to analyse the imposition of urban conservation-oriented controls in the city centre of Cape Town during the period 1986-2000 and to evaluate their efficacy; the secondary, but directly related endeavour, is to explore the effect of these mechanisms on development rights. In brief, the study set out to explore the themes "conservation constraints" and "development rights" and their relationship so that, ultimately, conclusions regarding the efficacy of the conservation-oriented controls can be drawn.